Northeastern mountain ponds as sentinels of change: Current and emerging research and monitoring in the context of shifting chemistry and climate interactions. (1st November 2021) - Nelson, S.J.; Hovel, R.A.; Daly, J.; Gavin, A.; Dykema, S.; McDowell, W.H.
Abstract: Mountain ponds in the northeastern US have undergone acidification and subsequent recovery due to changes in atmospheric deposition, and also reflect physical and biological responses to climate change. These ponds are distinct from other lakes and ponds in the region as they are higher in elevation, relatively small, and have little direct impact from human land use in their watersheds. They are vulnerable to the increases in extreme weather events, overall warming, and shortening of winter that are occurring throughout the northeastern US. We compiled data collected from 1978 to 2019 for mountain ponds >500 m elevation and <60 ha surface area across the northeastern US (Northern Appalachians and Adirondack Mountains). The full dataset includes 257 ponds; 36% of the sites were sampled at sufficient frequency to conduct trend analyses from the 1980s through 2010s. We found widespread, significant declines in sulfate concentrations (95% of sites, 44% decline) and significantly increasing ANC at 53% of sites (46% of sites-no trend; 1%-significant decrease). Significant declining conductivity at 97% of sites (33% decline) suggested dilution (14.0 μS/cm by the 2010s), and also reflected low chloride concentrations at these sites compared to others in the region affected by road salt contamination. DOC increased significantly in 54% of ponds (45% of sites-no trend; 1%-significant decrease). Increasing DOC has been attributed to both changing sulfate and climate related to increases in precipitation and air temperature. Other changes are occurring in these ponds alongside trends in water chemistry, such as thermal structures shifting as air temperature warms. Zooplankton communities are sensitive to water chemistry parameters associated with acidification recovery, such as DOC, but climate change may complicate transitions back to pre-acidification community composition. Based on this synthesis and a case study that integrates chemical, physical, and biological research, we developed a conceptual model and framework for research and monitoring to support measurements of change in these ecosystems. The findings indicate the importance of eastern mountain ponds in understanding combined impacts of atmospheric deposition and climate change on lake ecosystems and highlight future research directions. Graphical abstract: Image 1 Highlights: Northeastern US mountain ponds declined in sulfate, acidity, phosphorus over 40 years. Mountain ponds became more dilute, and showed widespread increasing DOC trends. Decline in monitoring efforts regionally, <20% of study locations recently sampled. Case study and conceptual model highlight influences on primary productivity, foodwebs. Warming, wetter climate produces novel conditions in ponds with legacy acidification.